Acessibilidade para pessoas com deficiência visual nas academias de musculação de Nova Prata/RS - Tomazi, Lutiene (My University, 2020)
The primary objective of this study was to analyze the accessibility of people with visual impairments (DV) in strength training gyms in the city of Nova Prata/RS. In addition, the study had as specific objectives to identify the gyms offering services to people with DV, to verify their demand for weight training, to observe and describe the architectural barriers for their access to these places, and to analyze the capacity of the instructors when supporting students with DV in the gym. The study was carried out in six gyms and with two participants with DV, in order to contribute with their perception regarding the aforementioned descriptors. This research is of qualitative, descriptive and transversal nature. Field observations and semi-structured interviews were used as approaches for data collection. As conclusion, people with visual impairment still face architectural and attitudinal obstacles in weight training gyms, where adaptations are necessary both in the physical space and in the care for this public. [resumo fornecido pelo autor]
O objetivo central deste estudo foi o de analisar a acessibilidade para pessoas com deficiência visual (DV) em academias de musculação no município de Nova Prata/RS. Além disso, o estudo teve como objetivos específicos identificar as academias que oferecem serviços a pessoas com DV, verificar a procura dos mesmos pela modalidade de musculação, observar e descrever as barreiras arquitetônicas de acesso nesses locais, e analisar a capacitação dos instrutores ao receber alunos com DV nas academias. O estudo foi realizado em seis academias e com dois participantes com DV a fim de contribuir com sua percepção referente aos assuntos retratados. A pesquisa foi de natureza qualitativa, descritiva e transversal. Foram utilizados como instrumentos para coleta de informações observações de campo e entrevistas semiestruturadas. Concluiu-se que as pessoas com DV ainda se deparam com obstáculos arquitetônicos e atitudinais em ambientes para praticar musculação, onde se fazem necessárias adaptações tanto no espaço físico quanto ao atendimento para esse público. [resumo fornecido pelo autor]
Keywords: Educação física; Academias de ginástica - Nova Prata (RS); Pessoas com deficiência - Orientação e mobilidade; Transtornos da visão